Penerapan Standardoperating Procedure Distribusi LPG 3kg Bersubsidi PT. Pondok Nikmah Jawahir Wilayah Kota Depok - Adinda Nina Safitri; Dewi Trirahayu (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Analysis of the Implementation of Standard Operating Procedures for the Distribution of Subsidized 3-Kg LPG at PT Pondok Nikmah Jawahir, Depok City The distribution of subsidized 3-kg LPG requires the consistent implementation of Standard Operating Procedures (SOPs) to ensure accurate delivery, workplace safety, orderly administration, and product availability for eligible consumers. This study aimed to analyze the implementation of SOPs for subsidized 3-kg LPG distribution at PT Pondok Nikmah Jawahir in Depok City and identify implementation gaps and appropriate improvement strategies. A qualitative approach with a descriptive method was employed. Data were collected through direct observation, interviews, documentation, benchmarking, and gap analysis. The data were analyzed through data condensation, data presentation, and conclusion drawing and verification. The findings indicate that most distribution activities were conducted in accordance with the SOPs established by PT Pertamina Patra Niaga, including cylinder receipt and inspection, storage, loading, delivery to authorized retailers, and reporting through the Pertamina MAP application. Nevertheless, several gaps were identified, including duplicated manual and digital administrative records, inconsistent use of personal protective equipment, the absence of systematically documented SOP compliance evaluations, and distribution delays caused by filling queues at LPG filling and transportation stations. The recommended improvements include simplifying digital administrative procedures, strengthening occupational safety supervision, establishing measurable SOP evaluation indicators, and improving coordination with filling stations and authorized retailers. Implementing these recommendations is expected to enhance the efficiency, safety, traceability, and accuracy of subsidized 3-kg LPG distribution.